2019
DOI: 10.3390/educsci9040287
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Conditions for Enhancing Critical Thinking in Networked Learning: Findings from a Secondary School Learning Analytics Environment

Abstract: Networked learning provides opportunities for learners to develop their critical thinking, an important 21st century competency, through dialogue with fellow learners to consider other perspectives and negotiate and critique ideas and arguments. However, much extant literature has not examined networked learning environments among younger learners nor the optimal conditions for enhancing critical thinking. Therefore, a study was carried out to investigate these conditions. A learning analytics networked learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
(79 reference statements)
0
6
0
1
Order By: Relevance
“…One possible explanation for this result is that learning analytics data may make students aware of their contribution in the discussion forum and allow them to evaluate themselves. Koh, Jonathan, and Tan (2019) found that learning analytics can increase critical thinking. This implies that students may find that learning analytics feedback helps them to reflect on their participation and improve the quality of their contribution in the discussion forum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation for this result is that learning analytics data may make students aware of their contribution in the discussion forum and allow them to evaluate themselves. Koh, Jonathan, and Tan (2019) found that learning analytics can increase critical thinking. This implies that students may find that learning analytics feedback helps them to reflect on their participation and improve the quality of their contribution in the discussion forum.…”
Section: Discussionmentioning
confidence: 99%
“…Learning analytics can be described as gathering, analysing, and reporting data related to learners' activities in an online learning environment (Siemens & Gašević, 2012). Learning analytics can be used as feedback to enhance the student learning process (Koh et al, 2019). Studies have found that learning analytics encourage student reflection, increase understanding and recognition of the learning process, and improve academic outcomes and achievements (Arnold et al, 2012).…”
Section: Learning Analytics and Student Participation In An Online Le...mentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of recent studies have explored the intersection of HOTS and LA. For example, visual LA tools have been used to investigate students' activities annotating reading materials and commenting on other annotations, which positively impact critical reading achievement (Koh et al, 2019). Learning assisted by visual LA tools also influences students' higher-order thinking (Zhang & Chan, 2020).…”
Section: Higher-order Thinking Skillsmentioning
confidence: 99%
“…Como recomendación final consideramos que, ante la participación del alumnado en las redes sociales la educación no debe mirar para otro lado y asumir una labor orientadora para garantizar un buen uso de las tecnologías (Colás et al, 2018;Plaza de la Hoz, 2018;Vázquez y Cabero, 2015;Koh et al, 2019) reconociendo que debe realizar una actividad enfocada a la prevención educativa para el consumo de medios digitales ante una gran diversidad de alumnos y alumnas, con distintas necesidades educativas, procedentes de diversas culturas y situaciones socio-económicas, donde se tiene que garantizar la igualdad de oportunidades y su papel compensador, de las desigualdades (Livingstone et al, 2019;Martínez-Piñeiro et al, 2018).…”
Section: Discusión Y Conclusionesunclassified